Numerical models in bioelectromagnetics - Dlugosz, Tomasz; Nichoga, Vitalij; Trzaska, Hubert (Видавництво Львівської політехніки, 2012)
The paper deals with problem of possible simplification of numerical models, especially in bioelectromagnetics, in order to shorten the calculation time and necessary RAM volume. Presented estimations confirm usefulness of presented idea.
Keywords: bioelectromagnetics; electromagnetic compatibility; numerical analysis